LANGUAGE REGISTER OF SUNDANESE STREET VENDORS IN GORONTALO CITY (SOCIOLINGUISTIC STUDY) - Elvira Nur Fathia; Dakia N. Djou; Asna Ntelu (RADJA PUBLIKA, 2025)
This study aims to (1) describe the forms of registers used by Sundanese street vendors in Gorontalo City and (2) describe the factors that influence the use of registers of Sundanese street vendors in Gorontalo City. This study uses a sociolinguistic approach based on Halliday's register theory. The method used in this study is a qualitative descriptive method. Data collection techniques are carried out through direct observation, listening to conversations, interviews, recordings, documentation. Data analysis techniques are carried out in 5 stages (1) transcribing the recording results, (2) translating, (3) identifying data, (4) grouping data, (5) analysis results and conclusions. The results of the study indicate that the form of language register used by traders consists of single and compound words that are functional, communicative, and adaptive to the surrounding environment. The vocabulary used reflects the characteristics of the Sundanese language. In addition, the use of this register is influenced by ethnic factors, social interaction, communication goals, and trade situations.